ARTIFICIAL INTELLIGENCE IN THE FIELD OF TAXATION (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article discusses the concept of artificial intelligence, its capabilities in the field of taxation, as well as problems that may arise in connection with the implementation of AI. An urgent task at the moment remains the creation of a law that would allow regulating relations in the field of artificial intelligence and robotics technologies.